2015
DOI: 10.1186/s12872-015-0082-5
|View full text |Cite
|
Sign up to set email alerts
|

Hyponatremia during hospitalization and in-hospital mortality in patients hospitalized from heart failure

Abstract: BackgroundTo date, the majority of studies on hyponatremia focussed on hyponatremia at admission, and came from developed countries. This study aimed to identify the prevalence of hyponatremia during hospitalization in patients hospitalized for HF and its association with in-hospital mortality.MethodsThis was an observational study using retrospective data from patients’ records between 2010–2013. It focused on those patients carrying an ICD-10 code of 150.0(Congestive Heart Failure) as their primary diagnosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
2
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 40 publications
2
14
2
3
Order By: Relevance
“…In our study, the prevalence of hyponatremia in patients admitted for AECOPD is 10.8% higher than that of patients with community-acquired pneumonia as reported by Cuesta et al [1], but lower than that of patients hospitalized for different causes, including AECOPD [2][3][4]23,24]. In addition to the low prevalence of hyponatremia, the absence of moderate and severe cases also seems noteworthy, despite the high percentage of patients with risk factors to develop it (heart failure, chronic kidney disease, cancer, and certain treatments).…”
Section: Discussioncontrasting
confidence: 57%
“…In our study, the prevalence of hyponatremia in patients admitted for AECOPD is 10.8% higher than that of patients with community-acquired pneumonia as reported by Cuesta et al [1], but lower than that of patients hospitalized for different causes, including AECOPD [2][3][4]23,24]. In addition to the low prevalence of hyponatremia, the absence of moderate and severe cases also seems noteworthy, despite the high percentage of patients with risk factors to develop it (heart failure, chronic kidney disease, cancer, and certain treatments).…”
Section: Discussioncontrasting
confidence: 57%
“…[39][40][41] A report from the HARVEST registry also revealed that hyponatremia and worsening sodium levels were associated with mortality in patients hospitalized for AHF. 42) In our results, serum sodium is considered to be an independent mortality predictor which was in relation to a 12.0% increase in mortality risk for each 1U decrease (HR 0.880, 95%CI 0.822-0.943).…”
Section: Discussionmentioning
confidence: 99%
“…Hyponatremia is the most common disorder of body fluid and electrolyte balance in hospitalized patients [ 1 ]. The presence of hyponatremia is hazardous since it is associated with increased risk of mortality in hospitalized patients [ 2 ], including those with heart [ 3 ] and liver [ 4 ] diseases, stroke [ 5 ], and chronic kidney disease (CKD) [ 6 , 7 ]. According to recent meta-analysis, hyponatremic subjects showed a 2.6 times higher risk of death than non-hyponatremic subjects, even when the decrease in the serum sodium level was moderate [ 8 ].…”
Section: Introductionmentioning
confidence: 99%